PREDICTING THE EFFECTS OF NUTRIENTS AND BIOACTIVE COMPOUNDS ON THE EXPRESSION OF LOW DENSITY LIPOPROTEIN RECEPTOR (LDLR) USING IN SILICO APPROACH - Musa, Ibrahim Suleiman; Okuba, Hafsat Ibrahim; Musa, Bilkisu Azores (FUDMA JOURNAL OF SCIENCES, 2024)
The objective of the study was to evaluate the effects of some nutrients and bioactive compounds on the expression of low density lipoprotein receptor using computational method. Low density lipoprotein accounts for 70% of circulating plasma cholesterol which is regulated by low density lipoprotein receptor. The evaluation of low density lipoprotein receptor expression was done using the Nutrigenome Data Base which is composed of manually curated differentially expressed genes from treatments with nutrients and bioactive compounds obtained from nutrigenomic experiments. Significant up regulation in the expression of low density lipoprotein receptor was associated with grape extract, quercetin, rosemary extract, tomato extract and sandal woods. Similarly, down regulation of LDLR expression was associated with yellow onion, cholic acid, gingerol and blackberry extract. It can be concluded that some nutrients and bioactive compounds present a great opportunity for the control of LDLR expression and hypercholesterolemia. Further studies on the use of locally available nutrients for the regulation of LDLR expression and hypercholesterolemia is recommended.